2020
DOI: 10.1037/adb0000546
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational congruence in adolescent onset of alcohol, tobacco, and marijuana use.

Abstract: We examined alcohol, tobacco, and marijuana (ATM) use onset across early to late adolescence in a sample of fathers and their offspring. We tested a theory of developmental congruence in polysubstance use, or the extent to which fathers’ ATM use onset in early adolescence increased risk for earlier ATM onset by their offspring. Average rates of adolescent ATM use onset were also compared across generations, which may reflect intergenerational discontinuity and secular trends. Children (n = 223, 44% boys) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…Household substance abuse predicted drugs consumption (but not alcohol consumption), supporting the intergenerational transmission found in previous studies in mainly English-speaking countries (Kerr et al, 2020;Langevin et al, 2019). In addition, substance abuse in the household also predicted deviant behavior in later development, as reported in other studies (Edwards et al, 2001;Muniz et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Household substance abuse predicted drugs consumption (but not alcohol consumption), supporting the intergenerational transmission found in previous studies in mainly English-speaking countries (Kerr et al, 2020;Langevin et al, 2019). In addition, substance abuse in the household also predicted deviant behavior in later development, as reported in other studies (Edwards et al, 2001;Muniz et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to other family dysfunctions, studies have mainly yielded mixed results regarding household substance abuse and intergenerational transmission (Langevin et al, 2019). The studies showing a positive link between the two variables showed that children whose parents consume illegal substances were more likely to also use drugs (Augustyn et al, 2020;Kerr et al, 2020). In some studies, this negative effect was even present across three generations (Neppl et al, 2020;Tiberio et al, 2020).…”
Section: Intergenerational Transmission and Household Dysfunctionsmentioning
confidence: 99%
“…First, we need better understanding of historic trends in use, what is contributing to these trends, and how those trends might impact future generations. As noted by Kerr et al (2020), we've observed a historic decrease in substance use among high school students since 1979 when substance use peaked (30-day alcohol and marijuana use for 12th graders). For example, past-30-day use of alcohol by 12th graders dropped from 71% in 1979 to 30% in 2018, a 60% decrease; likewise, we have observed a steep decline in binge drinking in the past 2 weeks from 41% to 17% (a 60% decrease).…”
Section: Implications For Future Researchmentioning
confidence: 76%
“…In comparison, children of chronic users were nearly 4.5 times as likely to use marijuana and 2.75 times as likely to use alcohol as children of nonusers. Kerr et al (2020) examined intergenerational associations in polysubstance use, grounding their work in developmental congruence theory. They found that children showed earlier alcohol, tobacco, and marijuana use onset if their fathers were early adolescent polysubstance users, compared to the late-adolescent primarily alcohol and tobacco users; mothers' alcohol, tobacco, and marijuana use in adolescence attenuated this effect.…”
Section: Key Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation